A cross sectional observational study to evaluate various cutaneous manifestations in geriatric age group - Krishna Talukdar; Debdeep Mitra (International Journal of Medical Research and Review, 2016)
Introduction: With an improvement in medical services and with increased life expectancy, in both developed and developing nations, the geriatric population is increasing and with this their medical needs including their cutaneous problems are also gaining more attention. This study highlights the various dermatoses prevalent in the geriatric population. Early detection of few of the dermatoses not only helps in their early treatment but also prevents further progression. Skin being the mirror of the internal body system often gives definitive clues for diagnosing several systemic ailments which are quite common in this age group. On the other hand skin is also at the receiving end and many systemic illnesses and medications modify the dermatological presentation in the elderly population.Methods: The geriatric patients (aged 60 years and above), attending Dermatology Out-patient Department in a tertiary hospital over a period of one year were included in this study. About 360 patients were included in this study.Results: Itching was the commonest presenting complaint and wrinkles were the commonest dermatological finding. Disorders of hair and nails was also were very common. A total of 7 patients out of the study group had malignant skin cancers and they were managed and followed up after the end of the study period to note any recurrence.Conclusion: The 60 and older patient population is a rapidly growing dermatology clientele with unique skin, hair, and nail issues. This study highlights the various dermatoses peculiar to the geriatric population and aims at sensitizing the fraternity to the specific needs of this special age group.